2022
DOI: 10.1111/pala.12586
|View full text |Cite
|
Sign up to set email alerts
|

Diversification dynamics of cheilostome bryozoans based on a Bayesian analysis of the fossil record

Abstract: Cheilostomata is the most diverse and ecologically dominant order of bryozoans living today. We apply a Bayesian framework to estimate macroevolutionary rates of cheilostomes since the Late Jurassic across four datasets: (I) manually curated genus ranges; (II) published text-mined genus ranges; (III) non-revised Paleobiology Database (PBDB) records; (IV) revised and augmented PBDB records. All datasets revealed increased origination rates in the Albian, and a twin K-Pg and Danian extinction rate peak. High ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 104 publications
1
9
0
Order By: Relevance
“…Fig. 3) mirroring well-established declines in diversity in all bryozoan groups (e.g., Håkansson & Thomsen, 1979McKinney & Taylor, 2001;Stilwell & Håkansson, 2012;Moharrek et al, 2022) and other marine groups. In Europe, the last Danian remnants of the Chalk Sea province were home to only a few, rare species (Berthelsen 1962;Kvachko 1995), while Selandian and Thanetian free-living bryozoans are even more scarce, with four Thanetian taxa reported from Deep Sea Drilling Project site 117 at Rockall Bank (Cheetham & Håkansson, 1972) constituting a post-Danian Paleocene 'hotspot'.…”
Section: Paleocenesupporting
confidence: 56%
“…Fig. 3) mirroring well-established declines in diversity in all bryozoan groups (e.g., Håkansson & Thomsen, 1979McKinney & Taylor, 2001;Stilwell & Håkansson, 2012;Moharrek et al, 2022) and other marine groups. In Europe, the last Danian remnants of the Chalk Sea province were home to only a few, rare species (Berthelsen 1962;Kvachko 1995), while Selandian and Thanetian free-living bryozoans are even more scarce, with four Thanetian taxa reported from Deep Sea Drilling Project site 117 at Rockall Bank (Cheetham & Håkansson, 1972) constituting a post-Danian Paleocene 'hotspot'.…”
Section: Paleocenesupporting
confidence: 56%
“…This produces high computational burden, and models for larger sampling regions could not be estimated efficiently. PyRate can alternatively use an efficient Gibbs algorithm to sample from the posterior distribution of the parameters, producing preservation-corrected estimates of origination and extinction times that are virtually identical to those from the Metropolis Hastings algorithm, but with a coarse birth-death model that involves a dramatic loss of resolution in the resulting rate curves 83 . A second programme, LiteRate, has been developed to permit origination and extinction rate estimation for taxonomically large datasets 24 , 25 , gaining computational efficiency by implementing the same birth-death model used by PyRate with the rjMCMC and Metropolis Hastings algorithm, but without estimation of the complex preservation model.…”
Section: Methodsmentioning
confidence: 99%
“…It was also suggested that endotrophic larvae could be advantageous at greater ocean depths where algal planktonic food is scarce [5]. One argument in favour of these hypotheses is that zygote-spawning malacostegans were (and still are) much less diverse and mostly occupy shallower habitats, while brooding neocheilostomes, which underwent a substantial radiation starting in the late Albian/ early Cenomanian [15,[19][20][21], still make up the vast majority of cheilostomes for all substrates and depths today.…”
Section: (D) Evolutionary Significance Of Parental Carementioning
confidence: 99%
“…By contrast, the more advanced neocheilostomes, all of which incubate their offspring and produce short-lived, non-feeding (=endotrophic, i.e. lecithotrophic or placentotrophic) larvae [5,[16][17][18], underwent a substantial radiation starting in the late Albian/early Cenomanian [15,[19][20][21] and make up the vast majority of extant cheilostomes. Although suborder Neocheilostomina d 'Hondt, 1985 [22] is not a currently accepted taxon name, 'neocheilostome' is a utilitarian term that will be used herein to refer to any cheilostome with an ovicell-a calcified brood chamber first found in the calloporid genus Wilbertopora from the late Albian [23].…”
Section: Introductionmentioning
confidence: 99%